2022
DOI: 10.1186/s10195-022-00678-z
|View full text |Cite
|
Sign up to set email alerts
|

Function and return to sports after proximal humeral replacement in patients with primary bone sarcoma

Abstract: Background Improved patient and limb survival rates have led to an increased interest in the functional outcome and return to sports of patients undergoing megaprosthetic reconstruction in musculoskeletal oncology. This study evaluates the functional outcome and postoperatively performed level of sports in patients undergoing proximal humeral replacement (PHR) following resection of a primary bone sarcoma and identifies potential beneficial and limiting factors. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Only a few studies have investigated the resumption of sporting activities following megaprosthetic reconstructions in oncological patient cohorts, although they have become increasingly important with the continuous improvements in patient life expectancy and quality of life [ 10 , 12 , 13 ]. For the upper extremity, Lang et al reported a return-to-sport rate of 100% in 18 patients who had undergone a proximal humeral replacement (PHR) after the resection of a primary bone sarcoma [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only a few studies have investigated the resumption of sporting activities following megaprosthetic reconstructions in oncological patient cohorts, although they have become increasingly important with the continuous improvements in patient life expectancy and quality of life [ 10 , 12 , 13 ]. For the upper extremity, Lang et al reported a return-to-sport rate of 100% in 18 patients who had undergone a proximal humeral replacement (PHR) after the resection of a primary bone sarcoma [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The WAS summarizes patients’ individual performance, by multiplying the frequency (sessions per week), duration (in hours), and impact of each performed sports activity (low-impact sports activity = 1, high-impact sports activity = 3; Table 2 ) [ 21 , 22 ]. The final WAS is obtained by adding the individual scores of each sports activity, whereby a WAS of 0–10 marks a low-activity patient, and a WAS of >10 denotes a high-activity patient [ 10 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Limb salvage treatment of the proximal humerus is a major surgical challenge, as it involves both the repair of bone defects and the reconstruction of shoulder joint function [ 4 , 8 , 9 ]. The shoulder joint is the joint with the largest range of motion in the human skeleton, and the rotator cuff and joint capsule are critical to its stability.…”
Section: Introductionmentioning
confidence: 99%